Log horizon. The West Wind Brigade. 3 - Touno, Mamare (Yen Press, 2016)
"A group of evil player killers is disrupting the peace, so it's the Brigade to the rescue--but awaiting them is a sinister trap. Guild master Soujirou must rise to the challenge (if only for the sake of the beautiful ladies in his guild)"--Amazon.com.